Heterogeneity in vascular smooth muscle cell embryonic origin in relation to adult structure, physiology, and disease. Issue 3 (March 2015) - Pfaltzgraff, Elise R.; Bader, David M.; Trainor, Paul; Johnson, Randy
<x xml:space="preserve">Abstract</x> Regional differences in vascular physiology and disease response exist throughout the vascular tree. While these differences in physiology and disease correspond to regional vascular environmental conditions, there is also compelling evidence that the embryonic origins of the smooth muscle inherent to the vessels may play a role. Here, we review what is known regarding the role of embryonic origin of vascular smooth muscle cells during vascular development. The focus of this review is to highlight the heterogeneity in the origins of vascular smooth muscle cells and the resulting regional physiologies of the vessels. Our goal is to stimulate future investigation into this area and provide a better understanding of vascular organogenesis and disease. Developmental Dynamics 244:410–416, 2015. © 2014 Wiley Periodicals, Inc.